Taxonomic revision of the Pirate Perches, Aphredoderus, (Percopsiformes: Aphredoderidae) with descriptions of two new species - Muller, Tyler A.; Simons, Andrew M. (Zootaxa, 2024)
Pirate Perches, Aphredoderus, are a widespread lowland freshwater fish native to the Eastern half of the United States. Aphredoderus was thought to contain a single species divided into an Eastern and Western subspecies on either side of the Appalachian Mountains with a widespread intergrade zone through much of the Eastern Gulf of Mexico and Southern Atlantic drainages. We use morphology and genetic data from specimens spanning the entire range of the genus to determine species limits within Aphredoderus. We find evidence of five species, four of which exhibit widespread sympatry in the Southeastern United States. We elevate A. sayanus sayanus and A. sayanus gibbosus to species, redescribe A. mesotrema, supplement previous descriptions, and describe two new species, A. retrodorsalis, and A. ornatus.